Respuesta :

9514 1404 393

Answer:

  x = 1

Step-by-step explanation:

You can work this several ways.

1) Consider the factor that gets you from the y-value of the known pair to the y-value of the unknown pair. Here, that factor is -6/12 = -1/2.

Then the unknown value of x is the known value multiplied by that same factor:

  x = (-1/2)(-2)

  x = 1

__

2) You can write the equation for a "varies directly" relationship and solve for the constant of proportionality. Then you can use that equation to find the unknown value of x.

  y = kx . . . . . . . . . . . . . . y varies directly with x

  k = y/x = 12/-2 = -6

Now we know ...

  y = -6x

Filling in the new value for y, we have ...

  -6 = -6x

  1 = x . . . . . . divide by -6

__

3) You can write a proportion. Since we want to find a value for x, it is convenient to put that in the numerator.

  -2/12 = x/-6

Multiplying by -6, we get ...

  (-6)(-2)/12 = x = 1

ACCESS MORE